Multicast sockets practical guide for programmers - Makofske, David B.; Almeroth, Kevin C. (San Francisco, CA : Morgan Kaufmann Publishers, 2003)
Multicast Sockets: Practical Guide for Programmers is a hands-on, application-centric approach to multicasting (as opposed to a network-centric one) that is filled with examples, ideas, and experimentation. Each example builds on the last to introduce multicast concepts, frameworks, and APIs in an engaging manner that does not burden the reader with lots of theory and jargon. The book is an introduction to multicasting but assumes that the reader has a background in network programming and is proficient in C or Java. After reading the book, you will have a firm grasp on how to write a multicast program. Features: * Author team of instructor and application programmer is reflected in this rich instructional and practical approach to the subject material * Only book available that provides a clear, concise, application-centric approach to programming multicast applications and covers several languagesC, Java, and CΔ on the .NET platform * Covers important topics like service models, testing reachability, and addressing and scoping. * Includes numerous examples and exercises for programmers and students to test what they have learned.
1 Introduction -- 1.1 Multicast Defined -- 1.2 Unicast vs. Multicast vs. Broadcast -- 1.3 The Multicast Tradeoff: Power/Flexibility vs. Complexity -- 1.4 An Overview of Multicast Protocols -- 1.5 Organization of this Book -- 2 Multicasting with C Sockets -- 2.1 UDP Sockets -- 2.2 Sending Multicast Packets in C -- 2.3 Receiving Multicast Packets in C -- 2.4 A Sample Run of Sender and Receiver(s) -- 2.5 C and Source Specific Multicast -- 2.6 WinSock Modifications -- 3 Multicasting with Java -- 3.1 The Java MulticastSocket API -- 3.2 A Java Multicast Sender -- 3.3 Receiving Multicast Packets in Java -- 3.4 A Sample Run -- 4 Multicasting with .NET -- 4.1 The .NET Sockets Class -- 4.2 Sending Multicast Packets in CΔ -- 4.3 Receiving Multicast Packets in CΔ -- 4.4 A Sample Run: CΔ Multicast Sender and Receiver -- 4.5 CΔ and Source Specific Multicast -- 4.6 The CΔ UdpClient Class -- 5 Source Specific Multicast -- 5.1 Source Specific Multicast Defined -- 5.2 Advantages of SSM -- 5.3 Host Support for SSM -- 5.4 SSM Additions to the APIs -- 6 Multicast Addressing and Scoping -- 6.1 Scoping -- 6.2 Multicast Address Space -- 6.3 Selecting a Multicast Address -- 6.4 Java Multicast Address Scope Methods -- 7 Multicast Reachability and Scalability -- 7.1 Multicast Reachability -- 7.2 Multicast Ping -- 7.3 Multicast Scalability -- 7.4 MPing with Receiver-based Congestion Control -- 8 Application Layer Multicast and Reflectors -- 8.1 Introduction -- 8.2 A Multicast Reflector in Java -- -- 9 Summarizing Lessons Learned -- A Multicast History and Protocols -- B Summary of Multicast API by Language.
Includes bibliographical references and index.
Keywords: Multicasting (Computer networks); Electronic books